DIRECT RATING METHOD UNTUK MENGUKUR EFEKTIVITAS IKLAN MELALUI MEDIA TELEVISI (STUDI PADA IKLAN TEH PUCUK HARUM): DIRECT RATING METHOD UNTUK MENGUKUR EFEKTIVITAS IKLAN MELALUI MEDIA TELEVISI (STUDI PADA IKLAN TEH PUCUK HARUM) - Hanifa, Fanni Husnul; Wulandari, Astri; Sastika, Widya (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2018)
ABSTRACT Advertising plays a role in the success of a company. Advertising can be presented through various media such as television. Many advertising is currently using social media and online media as a platform nowadays, but television is still use by companies to promote their products. Teh Pucuk Harum, as a new player in tea industry, has managed to become a top brand index in the past few years and currently a leader in the non-cup jasmine tea market. This study aims to determine the effectiveness of Teh Pucuk Harum advertisements through television media using direct rating method. The sub variables used are attention, read thoroughness, cognitive response, affective response and attitude response. The results of this study are total score of the entire sub variable of 84,075 which shows that Teh Pucuk Harum advertisement on television media in very good state.